Effects of Promethazine-Hydrochloride on Human Polymorphonuclear Leukocytes - DeChatelet, Lawrence R. (1973)
Promethazine hydrochloride at a concentration of 0.033 mg/ml has pronounced effects on leukocyte metabolism and function. The drug inhibits the phagocytosis-induced increases in O(2) consumption and hexose monophosphate shunt activity. Associated with these effects is an inhibition of the iodination of zymosan particles and an inhibition of bacterial killing by the cell. At least two mechanisms appear to be involved. Many of the effects can be explained by an inhibition of phagocytosis, but promethazine also inhibits the decarboxylation of amino acids and iodide fixation in a cell-free system, indicating a specific effect on metabolism. These results may partially account for the action of the drug in ameliorating the effects of erythroblastosis.